Rapid,va rog mult!
√9×5×√4×√1=
-3√7×5√2=
2(5√3+3√2)-10√3=
3√10-2(4√10+3)+5√10=
5√35×√5-6√21:(-2√3)+5√7=
Răspunsuri la întrebare
Răspuns de
1
Răspuns
Explicație pas cu pas:
√9×5×√4×√1=3*5*2*1=30
-3√7×5√2= -15 √14
2(5√3+3√2)-10√3=10√3 +6√2 -10√3 =6√2
3√10-2(4√10+3)+5√10=3√10-8√10 -6 +5√10 = -6
5√35×√5-6√21:(-2√3)+5√7=
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă